Systemic pharmacokinetic/pharmacodynamic analysis of intravitreal aflibercept injection in patients with retinal diseases. Issue 1 (20th March 2019) - Kaiser, Peter K; Kodjikian, Laurent; Korobelnik, Jean-Francois; Winkler, Julia; Torri, Albert; Zeitz, Oliver; Vitti, Robert; Ahlers, Cristiane; Zimmermann, Torsten; Dicioccio, A Thomas; Höchel, Joachim
Abstract : Objective: Explore relationships between systemic exposure to intravitreal aflibercept injection (IAI) and systemic pharmacodynamic effects via post hoc analyses of clinical trials of IAI for neovascular age-related macular degeneration (nAMD) or diabetic macular oedema (DME). Methods and analysis: Adults from VGFT-OD-0702.PK (n=6), VGFT-OD-0512 (n= 5), VIEW 2 (n=1204) and VIVID-DME (n=404) studies were included. Validated ELISAs were used to measure concentrations of free and bound aflibercept (reported as adjusted bound) in plasma at predefined time points in each study. Non-compartmental analysis of concentration–time data was obtained with dense sampling in VGFT-OD-0702.PK and VGFT-OD-0512. Sparse sampling was used in VIEW 2 and VIVID-DME. Blood pressure or intrarenal function changes were also investigated. Results: Following intravitreal administration, free aflibercept plasma concentrations quickly decreased once maximum concentrations were achieved at 1–3 days postdose; pharmacologically inactive adjusted bound aflibercept concentrations increased over a longer period and reached plateau 7 days postdose. Ratios of free and adjusted bound aflibercept decreased over time. There were no meaningful changes in systolic/diastolic blood pressure over the duration of each study at all systemic aflibercept exposure levels. For all treatment arms in VIEW 2, there was no clinically relevant change in mean intrarenal function from baseline at week 52. Overall, incidence of systemic adverse events in VIEW 2 and VIVID-DME was low and consistent with the known safety profile of IAI. Conclusion: IAI administration was not associated with systemic effects in patients with nAMD or DME as measured by blood pressure or intrarenal function, two known pharmacologically relevant effects of anti-vascular endothelial growth factor.